Dampak Penggunaan Perangkat Digital Interaktif Terhadap Perkembangan Motorik Halus Anak di Taman Kanak-Kanak (TK) - Fitriyani, Rini; Muthlifa, Alsa Alya; Margawati, Margawati (BOCAH: Borneo Early Childhood Education and Humanity Journal, 2025)
The rapid development of digital technology has influenced the way young children interact and learn, including in kindergarten settings. Interactive digital devices, such as tablets and touch screens, are now frequently used in children's learning and entertainment activities. However, attention to the impact on fine motor development is limited, despite this ability being essential to support writing readiness and other fundamental skills. This study aims to describe the effect of using interactive digital devices on children's fine motor development in kindergarten. The novelty of this research lies in the in-depth analysis of the direct experiences of teachers, children, and parents regarding the use of digital devices in everyday life. This study employs a descriptive qualitative approach, utilizing data collection techniques that include observation, interviews, and documentation. The research subjects were the children in Group B of one of the Aissiyah Kindergartens in Tenggarong District, Kutai Kartanegara, as well as the class teachers and parents, who served as supporting informants. Data validity is tested through source and technique triangulation. Data analysis was conducted thematically through the steps of data reduction, data presentation, and repeated drawing of conclusions. The findings suggest that excessive use of digital devices tends to decrease the frequency of manual activities essential for developing children’s fine motor skills. The implications of this study highlight the importance of striking a balance between technology and physical activities in the early childhood education curriculum.